Endovascular treatment of allogeneic kidney transplant artery stenosis - Szczerbiński, Jakub; Szlęzak, Ksawery; Bojakowski, Krzysztof; Andziak , Piotr (Wiedza Medyczna, 2023)
Recent studies have questioned the effectiveness of surgical treatment of renal artery stenosis. However, patients with artery stenosis of the solitary kidney may benefit most from endovascular therapy. Transplant renal artery stenosis is a cause of organ function deterioration, potentially leading to graft loss and increased mortality in the group of patients affected by this complication. However, we do not have data on the optimal treatment of transplant renal artery stenosis. Therapeutic methods includes conservative treatment and possible qualification for surgical treatment. Performing endovascular intervention offers the chance to correct the stenosis and return proper function to the transplanted kidney. Various methods are used during surgery: angioplasty, and stent implantation, including devices that release local antiproliferative drugs. At present, a timely intervention appears to offer the same chances of long-term graft function and survival as in kidney transplant recipients who do not develop TRAS. Data on epidemiology, risk factors and treatment outcomes are sparse, and further studies are needed.